The Relationship between Renewable Energy Consumption and Economic Growth in Azerbaijan - Mukhtarov, Shahriyar (International Journal of Energy Economics and Policy, 2022)
This article examines the causal relationship between renewable energy consumption and economic growth in case of Azerbaijan using annual data from 1992 to 2015. The Toda-Yamamoto causality test framework of vector autoregressive (VAR) model is utilized to test causal relationship between the variables. The results of this test reveal that there is unidirectional causality running from economic growth to renewable energy consumption. The study’s findings might be a helpful tool for Azerbaijani policymakers and oil-rich economies to make renewable energy-related policy decisions.